In-plane shear strength of solid clay brick masonry reinforced with near surface mounted steel bars - Armando Demaj; Ana Isabel Marques; João Gomes Ferreira; António Sousa Gago (Case Studies in Construction Materials, 2022)
Structural walls made of solid brick masonry have been used for centuries in old buildings, which are vulnerable to earthquakes. Reinforcing this type of walls may increase the overall building seismic strength. In this paper, the in-plane behaviour of these types of walls, both plain and reinforced, was experimentally assessed through triplets shear tests. The reinforcement considered, with near surface mounted (NSF) steel bars, has already been studied in the scope of a broader ongoing research project. The in-plane strength of brick masonry walls is of utmost relevance for seismic resistance and strongly depends on their resistance to sliding that may occur along the horizontal mortar interfaces. The bricks and the laying mortars tested correspond to walls of buildings built between 1920 and 1950 that may be found in Lisbon and other cities. Triplet specimens (made of three stacked bricks connected by a laying mortar) were built and tested. Two types of mortar compositions were used, of an earlier and a later phase within the period referred above. Both types included unreinforced specimens and specimens reinforced with steel bars of different types. The specimens were subjected to direct horizontal shear tests to determine the relevant properties of the assemblage, namely the cohesion and friction angle of the brick mortar joints. The results obtained in this study may be used in the numerical modelling of ancient buildings with brick masonry walls granting a better correlation with real behaviour.